The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/ndt.s128653
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of lamotrigine for all types of bipolar disorder

Abstract: BackgroundWe investigated whether the long-term efficacy and safety of lamotrigine (LTG) for bipolar disorder (BP) differs between disease types (BP-I, BP-II, or BP not otherwise specified [BP-NOS]), and the efficacy of the concomitant use of antidepressants (ADs).MethodsFor >1 year, we observed 445 outpatients with BP (diagnosed by DSM-IV criteria) who initiated LTG treatment between July 1 and October 31, 2011, using the Himorogi Self-rating Depression (HSDS) and Anxiety Scales and the Clinical Global Impres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…As noted previously, lamotrigine is utilized in other conditions characterized by dysregulated mood and poor impulse control, including bipolar disorder and BPD. When used in bipolar disorder, it is most notably effective in reducing depressive symptoms [29]. This ability to stabilize mood with potentially greater impact on depression [5557] may account for our exploratory and very preliminary findings of moderate reductions in depressive symptoms for some eating-disordered patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted previously, lamotrigine is utilized in other conditions characterized by dysregulated mood and poor impulse control, including bipolar disorder and BPD. When used in bipolar disorder, it is most notably effective in reducing depressive symptoms [29]. This ability to stabilize mood with potentially greater impact on depression [5557] may account for our exploratory and very preliminary findings of moderate reductions in depressive symptoms for some eating-disordered patients.…”
Section: Discussionmentioning
confidence: 99%
“…One such medication is lamotrigine, an antiepileptic drug. It has received FDA indication [28] for maintenance treatment of bipolar I disorder to delay the time to occurrence of mood episodes, and it is used widely for bipolar II disorder and unspecified bipolar and related disorders [29]. Lamotrigine also has shown promise in the treatment of borderline personality disorder (BPD) [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium nonresponsive conditions are chronic disorders that better respond to atypical neuroleptics, and have similarities to psychotic spectrum disorders [ 14 ]. Contrarily, some bipolar spectrum patients preferentially respond to anticonvulsants, as is the case with BD type II patients with comorbid anxiety disorders [ 15 ]. BD with psychotic symptoms has overlapping neurobiological findings with schizophrenia spectrum disorders, and such patients present with a higher risk of having family members with chronic, non-affective psychoses [ 16 ].…”
Section: Developmental Trajectory Of Mood Disordersmentioning
confidence: 99%
“…A Japanese observational study 56 reported findings for 445 patients with BD-I, BD-II or BD not otherwise specified (BD-NOS) who received LTG for 12 months (or until withdrawal), in most cases (77.5%), to supplement existing medication. Outcome measures were the Himorogi Self-Rating Depression Scale (HSDS), Himorogi Self-Rating Anxiety Scale and CGI-I.…”
Section: Resultsmentioning
confidence: 99%